Influence Of Physical Work Environment Factors, Equipment And Materials On Occupational Health And Safety In Ahass City Workshop Poor - Anas Firman Adi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In operate activity – activity his business, company must capable utilise source Power in the company. Wrong one of the most important aspects of resources within the company is the source Power man Which works as wheel drier activity company. One of the factors that can form satisfaction Work is the existence of guarantees and conditions Work Which comfortable for member organization. And K3 is wrong One factor Which can influence satisfaction Work .